The art of resilience (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Resilience is defined as "the capacity to recover quickly from difficulties; toughness; the ability to withstand adversity and bounce back from difficult life events." Whether it's fighting a wrong in the world, making a name for ourselves, or the everyday stresses of work, family, and the countless other obligations we have, we all face challenges. But we have to be able to overcome these adversities, adjust our course, and recover our spirits so we can press on with our lives and goals, and accomplish what we've set out to do. In this track, we draw on history to help us understand resilience, and look at some practical techniques to help anyone become more resilient. Learning Objectives Learn what resilience is Learn why resilience is important Learn actionable, easy-to-implement techniques that will help you build your resilience